A CASE OF RIGHT EXTERNAL INGUINAL HERNIA RELATED TO ENDOMETRIOSIS - SHIMOTSUMA, Masataka; AN, Byonggu; IZUMI, Hiroshi; TAKENAKA, Atsushi; FUJII, Kouji; OHGAKI, Masaharu (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2004)
We report a case of right external inguinal hernia related to endometriosis. A 30-year-old woman admitted for right inguinal pain during menstruation and a gradually enlarging bulge in the same region was found in pelvic CT to have a low-density mass that, based on this and the woman's clinical history, was diagnosed as right inguinal hernia related to endometriosis. Surgery showed a right external inguinal hernia containing old blood discharge. Histological examination of the hernia sac showed endometriosis in part of the sac. The round ligament of uterus was normal. Her postoperative course was uneventful. No signs of recurrence have been seen in the 2 months since surgery and right lower abdominal pain has almost completely disappeared.